Odpowiedź :
3√6-3 3√3
______ =------ = 1 Chyba o to ci chodziło tak?
√3 √3
______ =------ = 1 Chyba o to ci chodziło tak?
√3 √3
3√6-3 √3 3√18 -3 3√9*2 -3 6√2 -3 3√2
______ * __= ________= ________=________=______
√3 √3 √9 3 3 3
______ * __= ________= ________=________=______
√3 √3 √9 3 3 3
3√6 3√3
------ =----- = 1 (bo to się skróci)
3√3 3√3
nie wiem czy to tak ma być bo źle napisane a jeżeli taki przykład to dobrze
------ =----- = 1 (bo to się skróci)
3√3 3√3
nie wiem czy to tak ma być bo źle napisane a jeżeli taki przykład to dobrze